Analisis Yuridis Keabsahan Akta Jual Beli Hak Atas Tanah Sebagai Dasar Perjanjian Utang-Piutang Berdasarkan Undang-Undang Nomor 4 Tahun 1996 Tentang Hak Tanggungan - Wicaksana, Ikhlassul Daffa; Armanianto, Muhammad Eka; Mahmur, Muhamad (Wajah Hukum, 2026)
In debt arrangements where property ownership certificates are illegally transferred to creditors or other parties as collateral, which is contrary to Law Number 4 of 1996 concerning Lien Rights, the transfer of land rights through a deed of sale and purchase is sometimes used as a form of legal trickery. This study aims to analyze the implementation of Law Number 4 of 1996 concerning Lien Rights in cases of changes in the designation of collateral objects carried out through a Deed of Sale and Purchase based on debt, as well as the legal implications for parties harmed by inaccuracies in individual debt processes involving collateral objects represented by certificates transferred to names related to the Deed of Sale and Purchase. This paper analyzes the legality and application of Law Number 4 of 1996 concerning Lien Rights through normative legal research. The research findings indicate that liens are the only legitimate source of collateral, so the use of a sale and purchase basis for the transfer of land rights in debt agreements is illegal. Decisions 75/Pdt.G/2016/PN.Krg and 46/PDT/2020/PT YKK indicate that issuing certificates to creditors without following mortgage procedures is detrimental to debtors and is considered null and void, thus creating legal risks. This study emphasizes the need to comply with Article 1320 of the Indonesian Criminal Code and the provisions of the Mortgage Law to provide justice and legal protection for all parties involved. Furthermore, to provide law enforcement authority to creditors and ensure clear legal protection for debtors, the certificate must be registered as a Mortgage Right at the Land Office. Consequently, incorporating mortgage rights into debt agreements can reduce legal ambiguity, increase legal clarity, and prevent losses.